ANALISIS FAKTORFAKTOR YANG MEMPENGARUHI PENAWARAN KREDIT PADA BANK UMUM - Olga Fatima Da Costa Soares, 09.05.51.0002; Parmono Hadi, Teguh (Students Journal of Economic and Management, 2012)
This study aims to determine the effect variable DPK, CAR, NPL, and SBI to the distributions of banking credit principal to Commercial Bank in Indonesia during the period 2005-2009. This research analyzed by multi regression analysis using SPSS program. The result showed that not all variable positifely and significantly influence the banking credit.